Evaluation of the impact of the COVID-19 pandemic on the financial health of commercial insurance companies in the Czech Republic - Přečková, Lenka; Vávrová, Eva (Research Papers in Economics and Finance, 2024)
This article focuses on assessing the impact of the COVID-19 pandemic on the insurance operations of commercial insurance companies in the Czech Republic. The aim of the article is to determine the impact of the pandemic on the financial health of commercial insurance companies in the Czech Republic. In order to achieve this, ratio indicators suitable for measuring the financial health of commercial insurance companies, such as the growth rate of premium income, cost-effectiveness, profitability or solvency, have been employed. Because insurance activities in non-life and life insurance differ and show different values of ratio indicators of financial health, insurance companies have been divided into two groups: those with a predominance of life insurance and those with a predominance of non-life insurance. The impact of the pandemic on the financial health indicators of individual commercial insurance companies has been monitored. The period from 2016 to 2021 has been selected to determine the impact of the pandemic. The authors have used data from the statistics of the Czech Association of Insurance Companies and annual reports of insurance companies.